PENYULUHAN PEMBUATAN AMELIORAN SEBAGAI BAHAN PEMBENAH TANAH DI DESA PEMENANG BARAT - Astiko, Wahyu; Fauzi, M. Taufik; Sudantha, I Made; Sudirman, Sudirman; Ernawati, Ni Made Laksmi; Muthahanas, Irwan (Jurnal Pepadu, 2024)
Pemenang Barat Village is one of the villages in the North Lombok Region whose land is dominated by sandy soil, has a dry climate and low rainfall. This sandy soil is porous, poor in nutrients and organic matter. This condition causes plant growth and yield to be low and can even cause harvest failure. Through this community service activity, "Instruction on the Making of Ameliorant as a Soil Improvement Material has been carried out in the West Pemenang Village". Activity methods are lecture, discussion, question and answer, demonstration and practice. This extension activity went well, the extension participants were active and enthusiastic in participating in the discussion. The results of this counseling can be concluded that there has been an increase in participants' understanding and skills regarding making ameliorant as a soil improver that can increase soil fertility.